Reliability of the physiological and metabolic responses to a field hockey specific treadmill protocol for elite female players - Macleod, H.; Sunderland, C. (The Journal of Sports Medicine and Physical Fitness, 2012)
AIM: The purpose of this study was to assess the reliability of the physiological and metabolic responses to a sport-specific treadmill protocol designed to simulate the activity pattern of elite women`s field hockey match-play. METHODS: Eight elite female field hockey players completed two trials of the Field Hockey Intermittent Treadmill Protocol (FHITP) separated by 5 days. The protocol consisted of 50 min of intermittent treadmill running designed to replicate the demands of match-play. Heart rate was determined continuously using Polar Team monitors. Rectal temperature was recorded every 10 min and capillary blood samples were taken at rest, at half-time (immediately after the completion of the first half) and at the end of the protocol for analysis of blood glucose and lactate. RESULTS: Heart rate response (CV 3.5%, CI, 2.9% to 4.4%), rectal temperature (CV 0.6%, 95% CI, 0.5% to 0.8%) and blood glucose (CV 1.4%, 95% CI, 1.1% to 2.1%) were all reproducible. No systematic error was evident between trials for blood lactate response (P=0.289) to the FHITP, although the overall CV for the measurement was 14.2% (95% CI, 10.7% to 21.2%). CONCLUSION: It was concluded that the physiological and metabolic responses to the FHITP were highly reproducible with the recommendation that blood lactate concentrations are used in conjunction with heart rate or other key performance measures to assess performance.